Speaking Across Faiths: A Critical Discourse Analysis of Interfaith Dialogue in American Cultural Context - Roselani, Ni Gusti Ayu; Surtantini, Rin (Crises on Languages and Literature, 2025)
Grounded in Fairclough’s Critical Discourse Analysis (CDA), this study examines an interfaith public dialogue by integrating Hyland’s metadiscourse framework and multimodal discourse analysis, with particular attention to linguistic stance-taking, spatial arrangement, and audience engagement. Framed as a conversation, the event reflects broader American discourse norms that privilege civility, authenticity, and pluralistic cooperation over institutional authority. Methodologically, the research adopts a descriptive qualitative approach, incorporating corpus-based concordance data to support close textual analysis without pursuing full quantification. Drawing on visual grammar (Kress & van Leeuwen, 2006) and U.S. pluralism principles (Interfaith America, 2022), the study investigates how the speakers negotiate theological disagreement not only through verbal choices but also through spatial positioning, humor, and reflexivity. The findings reveal how strategic spatial positioning, reflexive metadiscourse, and humor can soften theological tensions and foster dialogic engagement. In the analyzed event, these strategies were particularly evident in the Muslim speaker’s interactional choices, illustrating how multimodal cues mediate disagreement and build rapport. The study underscores that interfaith dialogue is co-constructed through both textual and embodied resources, offering practical insight into designing inclusive and relationally attuned interfaith encounters.